PENGARUH LATIHAN IN OUT SHUFFLE “AGILITY LADDER DRILL” TERHADAP KELINCAHAN SSB SPN U-17 PEKANBARU - Muhammad Firdaus; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problems in the study of the SSB SPN U-17 Pekanbaru is still of theplayers SSB SPN U-17 Pekanbaru such, it is seen to be done from various tests andofficial competitions, so the lack of maneuverability is a factor contributing to thedefeat. The purpose of this research was to observe the effect of practice side right in“agility ladder drill” of agility on SSB SPN U-17 Pekanbaru football club withrespondents 16 people. Sampling techniques using total sampling, where the totalpopulation is sampled. Data collection techniques derived from the pre-test and posttest. Instrument in this research using Illinois agility run test to see agility. Analyseswere performed using t-test. Based on data analysis and discussion it can be concludedthat there is significant effect from a exercises in out shuffle “agility ladder drill” toagility in Pekanbaru SBB SPN U-17 football club as evidence by Ttest 4.91 and Ttable1.75. it means Ttest > Ttable at the level of α=0.05Keyword : in out shuffle “agility ladder drill”, agility, football